‘Indirect Feedback’ - Ricardo Tejeiro; Dimitrios Vlachopoulos; Anthony Edwards; Estefania Campos (Higher Learning Research Communications, 2019)
Whilst there is consensus in the current literature that feedback plays a fundamental role to student performance and learning, there is also debate about what makes it effective. Particularly, some assessment instruments, like the National Student Survey in the United Kingdom, reveal that evaluation and feedback are systematically amongst the areas that students are less satisfied with. This paper aims to describe the ‘indirect feedback’ (IF) technique, which was utilised by the principle author in his previous tenure as a Professor at the University of Cadiz (Spain) and to reflect on how it can be applied to overcome some of the limitations presented in a different ‘context of practice’. It is argued that indirect feedback meets many of the principles of good practice, as it “facilitates the development of self-assessment (reflection) in learning, delivers high quality information to students about their learning, encourages teacher and peer dialogue around learning … provides opportunities to close the gap between current and desired performance [and] provides information to teachers that can be used to help shape their teaching” (Nicol & MacFarlane-Dick, 2006, p. 205).